Fulminating septic shock from Clostridium perfringens in an early breast cancer patient with severe myalgia after docetaxel treatment - Alessandro Marco Minisini; Jessica Menis; Alessandro Follador; Claudio Avellini; Gianpiero Fasola (Clinics and Practice, 2011)
Anaerobic bacteraemia could be a lifethreatening condition in neutropenic patients receiving chemotherapy. Taxane therapy is associated with necrotising inflammation of the caecum (named also typhlitis) that could be a potential source for bacteraemia. We report the case of a sudden onset of septic shock by Clostridium perfringens in a young patient treated with docetaxel as adjuvant chemotherapy for early breast cancer. A minireview of the literature has been performed.